Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Tìm X
a) \(2x+\dfrac{3}{24}=3x-\dfrac{1}{32}\)
\(\Leftrightarrow\left(2x+\dfrac{3}{24}\right)-\left(3x-\dfrac{1}{32}\right)=0\)
\(\Leftrightarrow2x+\dfrac{3}{24}-3x+\dfrac{1}{32}=0\)
\(\Leftrightarrow\left(\dfrac{3}{24}+\dfrac{1}{32}\right)+\left(2x-3x\right)=0\)
\(\Leftrightarrow\dfrac{5}{32}-x=0\)
\(\Leftrightarrow x=\dfrac{5}{32}\)
a) (x+2) + (x+3) + (x+5) = 25
3x + 10 = 25
3x = 15
x = 5
b) 62 - 3.(x+2) = 52.2
62 - 3.(x+2) = 50
3.(x+2) = 12
x+2 = 4
x = 2
c) 25 - (2x+3) = 16
25 - 2x - 3 = 16
22 - 2x = 16
2x =6
x = 3
a) 4.25-12.5+170:10
=100-60+17
=40+17
=57
b) (7+33:32).4-3
=(7+3).4-3
=10.4-3
=40-3
=37
c) 12:{400:[500-(125+25.7)]}
=12:{400:[500-(125+175)]}
=12:{400:[500-300]}
=12:{400:200}
=12:2
=6
d) 168+{[2.(24+32)-2560]:72}
=168+{[2.(16+9)-1]:49}
=168+{[2.25-1]:49}
=168+{[50-1]:49}
=168+{49:49}
=168+1
=169
a) \(A\left(x\right)=x^2-10x+25\)
\(\Rightarrow A\left(x\right)=\left(x-5\right)^2\)
\(\Rightarrow\left\{{}\begin{matrix}A\left(0\right)=\left(0-5\right)^2=25\\A\left(-1\right)=\left(-1-5\right)^2=36\end{matrix}\right.\)
b) \(A\left(x\right)+B\left(x\right)=6x^2-5x+25\)
\(\Rightarrow B\left(x\right)=6x^2-5x+25-A\left(x\right)\)
\(\Rightarrow B\left(x\right)=6x^2-5x+25-\left(x^2-10x+25\right)\)
\(\Rightarrow B\left(x\right)=6x^2-5x+25-x^2+10x-25\)
\(\Rightarrow B\left(x\right)=5x^2+5x\)
\(\Rightarrow B\left(x\right)=5x\left(x+1\right)\)
c) \(A\left(x\right)=\left(x-5\right)C\left(x\right)\)
\(\Rightarrow C\left(x\right)=\dfrac{\left(x-5\right)^2}{x-5}=x-5\left(x\ne5\right)\)
d) Nghiệm của B(x)
\(\Leftrightarrow B=0\)
\(\Leftrightarrow5x\left(x+1\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=0\\x+1=0\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}x=0\\x=-1\end{matrix}\right.\) là nghiệm của B(x)
a) \(\left(x-2\right)\left(x+1\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x-2=0\\x+1=0\end{matrix}\right.\) \(\Leftrightarrow\left[{}\begin{matrix}x=2\\x=-1\end{matrix}\right.\)
b) \(\left(x^2+5\right)\left(x^2-25\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x^2+5=0\\x^2-25=0\end{matrix}\right.\) \(\Leftrightarrow\left[{}\begin{matrix}x^2=-5\\x^2=25\end{matrix}\right.\) \(\Leftrightarrow x^2=25\) \(\Leftrightarrow x=\pm5\)
| 25 - x2 | = | 5 - x |
\(\Rightarrow\orbr{\begin{cases}25-x^2=5-x\\25-x^2=x-5\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}x^2-x=25-5\\x+x^2=25+5\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}x.\left(x-1\right)=20\\x.\left(x+1\right)=30\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}x.\left(x-1\right)=4.5\\x.\left(x+1\right)=5.6\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}x=5\\x=5\end{cases}}\Leftrightarrow x=5\)